Efficient Synthesis of Novel Triazolo[5,1-b]purines by Diacetoxyiodobenzene-Mediated Oxidative Cyclization of Schiff Bases - Artyom O. Neymash; Victor V. Fedotov; Evgeny N. Ulomsky; Daniil N. Lyapustin; Semen V. Aminov; Vladimir L. Rusinov (Reactions)
In this work, we have developed a method for synthesizing new 8-substituted triazolo[5,1-b]purines using diacetoxyiodobenzene as an oxidizing agent with good yields (59–67%). The advantages of this approach include mild reaction conditions and removing the need to use transition metals. Based on the results obtained, a plausible reaction pathway was proposed. The developed approach opens new possibilities for the preparation of previously inaccessible condensed purine derivatives, which are of interest for the development of biomolecules with a variety of pharmacological applications. The structures of the compounds were confirmed by the data of 1H, 13C NMR spectroscopy, IR spectroscopy, and an elemental analysis.